EFFECTIVENESS OF PHYSICAL EDUCATION EXERCISES FOR PRESCHOOL CHILDREN WITH PECTUS CARINATUM (CHEST WALL DEFORMITY) (World Bulletin of Physical Education and Sports Science, 2026)
This study aimed to evaluate the effectiveness of physical education exercises in the treatment of pectus carinatum (chest wall deformity) in preschool children. A total of 60 children participated in a 12-week exercise program. The results showed significant improvements in muscle tone, posture, and motor coordination (p < 0.05). The findings confirm the effectiveness of exercise therapy as a conservative treatment method that contributes to children’s physical development.
Keywords: Preschool children, pectus carinatum, physical education, exercises, muscle tone, posture, motor coordination.